Single-stage input-current-shaping technique with voltage-doubler-rectifier front end. - Jindong Zhang
In this paper, a new single-stage input-current-shaping (S2 ICS) technique that integrates the voltage-doubler-rectifier front end with a DC/DC output stage is introduced. Due to the voltage-doubler-rectifier front end, a reduction of line-current harmonics can be achieved with a higher conversion efficiency compared to the corresponding S2ICS circuit with the conventional wide-range full-bridge rectifier. The proposed technique requires energy-storage capacitors with the same total capacitance and with half of the voltage rating as in the conventional S2ICS counterpart, which reduces the size and cost of the power supply. The performance of the proposed technique is evaluated on a 450 W (5 V/90 A) experimental prototype circuit
Keywords: 450 W; 5 V; 90 A; AC-DC converter; DC/DC output stage; Energy-storage capacitors; Line-current harmonics reduction; Power factor correction; Single-stage input-current-shaping technique; Voltage-doubler-rectifier front end; Wide-range full-bridge rectifier